Losses to follow-up of HIV-infected people in the Spanish VACH cohort over the period between 2013 and 2014: The importance of sociodemographic factors - Teira, Ramón; Espinosa, Nuria; Gutiérrez, M. Mar; Montero, Marta; Martínez, Elisa; González, Francisco; Lozano de León, Fernando; Téllez, Francisco; Galindo, M. José; Peraire, Joaquim; Deig, Elisabeth; Muñoz-Sánchez, Pepa (Enfermedades infecciosas y microbiologia clinica (English ed.), 2019)
To determine the proportion of people infected by HIV or AIDS under follow-up in the VACH Cohort in 2012 who were lost to follow-up from 2013 to 2014, and to establish the sociodemographic features relating to this loss. We considered subjects with less than one recorded consultation per year studied to be lost to follow-up. We built logistic regression models to calculate the odds ratios (OR) and their 95% confidence intervals (95% CI), of the variables relating to loss to follow-up. The overall percentage of losses to follow-up was 15.5% (95% CI 14.9–16.1). The variables associated with loss to follow up were: not receiving antiretroviral treatment (ART) (OR: 1.948, 95% CI: 1.651–2.298), being an immigrant (OR: 1.746, 95%CI: 1.494–2.040), intravenous drug consumption being the mechanism for HIV transmission (OR: 1.498, 95% CI: 1.312–1.711), being unemployed (OR: 1.331, 95% CI: 1.179–1.503), being without a partner (OR: 1.948, 95% CI: 1.651–1.298), belonging to a low socioeconomic class (OR: 1.279, 95% CI: 1.143–1.431), and being attended in a hospital with fewer than 1000 patients under follow-up (OR: 1.257, 95% CI: 1.121–1.457), as well as being under age and having spent less time under follow-up in the Cohort. 15.5% of the patients were lost to follow-up over a period of 2years in the VACH Cohort. This was associated with a series of sociodemographic and epidemiological variables that it might be useful to identify to design initiatives targeting the populations most likely to abandon the circuits of care, and guide strategies towards achieving Objective 90-90-90. Determinar la proporción de personas con infección por VIH o sida que se encontraban en seguimiento en la cohorte VACH en 2012 y que resultaron perdidas del mismo en 2013 y 2014, así como establecer las características sociodemográficas relacionadas con dicha pérdida. Consideramos perdidos del seguimiento a los sujetos con menos de un registro de consulta por año analizado. Construimos modelos de regresión logística para la estimación de las razones de ventajas (odds ratio [OR]) y sus intervalos de confianza del 95% (IC del 95%) de las variables relacionadas con la pérdida de seguimiento. El porcentaje global de pérdidas en seguimiento fue del 15,5% (IC del 95%: 14,9-16,1). Las variables asociadas con la pérdida de seguimiento fueron no recibir tratamiento antirretroviral (TAR) (OR: 1,948; IC del 95: 1,651-2,298), ser inmigrante (OR: 1,746; IC del 95: 1,494-2,040), el consumo de fármacos por vía intravenosa como mecanismo de transmisión del VIH (OR: 1,498; IC del 95: 1,312-1,711), encontrarse en situación de desempleo (OR: 1,331; IC del 95: 1,179-1,503), no tener pareja (OR: 1,948, IC del 95: 1,651-1,298), pertenecer a un estrato socioeconómico bajo (OR: 1,279; IC del 95: 1,143-1,431) y ser atendido en un hospital con menos de 1.000 pacientes en seguimiento (OR: 1,257; IC del 95%: 1,121-1,457), además de menor edad y menos tiempo de seguimiento en la cohorte. El 15,5% de los pacientes fueron perdidos del seguimiento en un periodo de 2años en la cohorte VACH. Ello se asoció a una serie de variables sociodemográficas y epidemiológicas, cuya identificación puede ser útil para diseñar iniciativas focalizadas sobre las poblaciones más susceptibles de abandonar los circuitos asistenciales y a orientar estrategias diseñadas a la consecución del objetivo 90-90-90.